Identification and characterization of the Remorin gene family in Saccharum and the involvement of ScREM1.5e-1/-2 in SCMV infection on sugarcane - Yang, Zongtao; Cheng, Guangyuan; Yu, Quanxin; Jiao, Wendi; Zeng, Kang; Luo, Tingxu; Zhang, Hai; Shang, Heyang; Huang, Guoqiang; Wang, Fengji; Guo, Ying; Xu, Jingsheng (Frontiers in Plant Science, 2024)
Remorins (REMs) are plant-specific membrane-associated proteins that play important roles in plant-pathogen interactions and environmental adaptations. In this study, 65 REMs were identified from Saccharum spontaneum genome and classified into six groups based on phylogenetic tree analysis. These REMs contain multiple cis-elements associated with growth, development, hormone and stress response. Expression profiling revealed that among different SsREMs with variable expression levels in different developmental stages or different tissues. A pair of alleles, ScREM1.5e-1/-2, were isolated from the sugarcane cultivar ROC22. ScREM1.5e-1/-2 were highly expressed in leaves, with the former expressed at significantly higher levels than the latter. Their expression was induced by treatment with H2O2, ABA, ethylene, brassinosteroid, SA or MeJA, and varied upon Sugarcane mosaic virus (SCMV) infection. ScREM1.5e-1 was localized to the plasma membrane (PM), while ScREM1.5e-2 was localized to the cytoplasm or nucleus. ScREM1.5e-1/-2 can self-interact and interact with each other, and interact with VPgs from SCMV, Sorghum mosaic virus, or Sugarcane streak mosaic virus. The interactions with VPgs relocated ScREM1.5e-1 from the PM to the cytoplasm. These results reveal the origin, distribution and evolution of the REM gene family in sugarcane and may shed light on engineering sugarcane resistance against sugarcane mosaic pathogens.